The changing birth suite experience for Australian medical students. (28th July 2016) - Hogan, Emma; Woods, Cindy; Buttrose, Maryke; Abenthum, Linda; Cheng, Hon C.; de Costa, Caroline
Abstract : Competition with midwifery students, combined with increasing numbers of medical students, has led to declining standards of clinical experience in the birth suite for our senior medical students. In the Australian setting, increased and improved communication and collaboration between the two disciplines is urgently needed to rectify the situation.